Comparison of hypertensive outcomes after the implementation of self-management program for older adults with uncontrolled hypertension in Krabi, Thailand: a quasi-experimental study - Saowaluck Sukpattanasrikul (2022)
Purpose: This study aims to examine the effects of a self-management program (SMP) on self-care behavior, blood pressure and quality of life among older adults with uncontrolled hypertension. Design/methodology/approach: A quasi-experimental design with repeated measures was conducted in two primary care units in Krabi, Thailand. One hundred and fifty-six older adults with uncontrolled hypertension were selected based on the inclusion criteria and divided into experimental and control groups with 78 participants in each. The experimental group received the SMP, including the intervention related to the self-management process (from the 1st to 4th weeks) and a follow-up phase (from the 5th to 16th weeks). The control group received standard care. The outcomes were measured over time, including self-care behavior (baseline, 4th and 16th weeks), blood pressure (baseline, 4th, 8th, 12th and 16th weeks) and quality of life (baseline and 16th week). Findings: The generalized estimating equations showed that the SMP, compared with the control group, statistically significantly improved self-care behavior (p < 0.001), decreased blood pressure (p < 0.001) and improved quality of life (p < 0.001) at the 16th week. Originality/value: The SMP improved the self-care behavior, decreased blood pressure and improved the quality of life among older adults with uncontrolled hypertension. Registered nurses could administer this program for long-term benefits and help reduce the burden on primary care services.